2019
DOI: 10.1523/jneurosci.1392-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Activation of GluN2C/GluN2D-Containing NMDA Receptors by Ambient Glutamate Facilitates Cortical Interneuron Maturation

Abstract: Developing cortical GABAergic interneurons rely on genetic programs, neuronal activity, and environmental cues to construct inhibitory circuits during early postnatal development. Disruption of these events can cause long-term changes in cortical inhibition and may be involved in neurological disorders associated with inhibitory circuit dysfunction. We hypothesized that tonic glutamate signaling in the neonatal cortex contributes to, and is necessary for, the maturation of cortical interneurons. To test this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 90 publications
2
83
0
Order By: Relevance
“…Our findings demonstrate that both GluN2C/D-mediated potentiated excitatory drive (EPSCs) and enhanced intrinsic excitability act synergistically to increase the output of this neuronal functional class. The addition of CIQ (+) depolarized the resting membrane potential of FSINs, suggesting GluN2C/D-containing receptors are active at rest, as has been reported in interneurons of the developing cortex [37]. This unique feature of GluN2C/D-containing NMDARs can be attributed to basal glutamatergic tone acting with higher potency (~0.5 μM) at GluN2D-containing NMDARs, which are active at rest due to weak Mg 2+ -induced rectification [20,38].…”
Section: Plos Onesupporting
confidence: 61%
“…Our findings demonstrate that both GluN2C/D-mediated potentiated excitatory drive (EPSCs) and enhanced intrinsic excitability act synergistically to increase the output of this neuronal functional class. The addition of CIQ (+) depolarized the resting membrane potential of FSINs, suggesting GluN2C/D-containing receptors are active at rest, as has been reported in interneurons of the developing cortex [37]. This unique feature of GluN2C/D-containing NMDARs can be attributed to basal glutamatergic tone acting with higher potency (~0.5 μM) at GluN2D-containing NMDARs, which are active at rest due to weak Mg 2+ -induced rectification [20,38].…”
Section: Plos Onesupporting
confidence: 61%
“…A recent study in mouse cortex has revealed that parvalbuminergic interneurons mature via tonically active GluN2C/2D-containing receptors which transform the depolarizing signaling of ambient glutamate into an increase of dendritic complexity. Interestingly, the action is temporally limited to an early postnatal time window: a pharmacological block of GluN2C/2D receptors between day 7 and 9 yields at day 21 interneurons with less dendritic branch points and reduced inhibitory activity (Hanson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mature interneurons where iGluRs differentially contribute towards synaptic transmission, immature and migrating interneurons express different glutamate receptor subunits including the NMDA-type iGluR (NMDAR) and AMPA/Kainate-type iGluR (AMPAR/KAR) [1315] prior to the expression of any functional synapses. This becomes particularly important as the developing brain contains higher ambient glutamate levels than the adult brain [16]. Collectively, higher ambient glutamate, developmental expression of iGluRs and recruitment of glutamatergic signaling is considered to be trophic [8, 17, 18] and thought to engage mechanisms to regulate various aspects of interneuron development including morphological and electrical maturation to promote appropriate circuit integration [9, 11, 14, 16, 1922].…”
Section: Introductionmentioning
confidence: 99%